Dielectric properties of a monolayer nano-graphyne structure: Monte Carlo simulations - Fadil, Z.; Mhirech, A.; Kabouchi, B.; Bahmad, L.; Ousi Benomar, W. (Superlattices and microstructures, 2019)
In this paper, the dielectric properties of a monolayer nano-graphyne structure, with mixed spins σ = 7/2 and S = 1, have been studied, using Monte Carlo simulations. Firstly, the ground state phase diagrams for a zero temperature value are reported and discussed. Secondly, the dielectric properties of the studied system for a non-zero temperature are examined. The effects of the temperature, the external longitudinal electric and crystal fields on polarization, dielectric susceptibility and hysteresis cycles have been investigated. •The thermodynamic and dielectric properties of a monolayer nano-graphyne structure using Monte Carlo simulations are investigated.•The ground state phase diagrams are presented and discussed.•Blocking temperature has been deduced for different physical parameters.•The hysteresis cycles of a monolayer nano-graphyne structure are analyzed.